Exchange Rate Regime in China - Šplíchal, Václav; Taušer, Josef; Čajka, Radek, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
This master's thesis deals with the topic of the exchange rate regime in China. The aim of this paper is to analyse and to elaborate the regime under which the Chinese official currency is traded and managed as well as to assess to what degree the rate is artificially manipulated. The thesis consists of four chapters that present both theoretical background of the field and practical comparative analysis. The first chapter explains the theoretical background of the topic, basics and purpose of exchange rates and different regimes under which exchange rates are managed. Second chapter illustrates the history of the Renminbi, its first issues and significant interventions made by the government as well as growing level of its internationalisation. Third chapter analyses Chinese balance of payments and its foreign exchange reserves and compares them to other economies. Last chapter of the paper assesses whether the Renminbi is undervalued with the help of fundamental equilibrium exchange rate approach introduced by a study of William Cline and John Williamson.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses